Structural Equation Model of Variables that Influence Thai Fast Food Restaurant Brand Loyalty (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Thailand's 'street food is world-renowned for its profusion of exotic flavors and fragrances, making Thai food one of the most sought-after of international cuisines. Therefore, the authors examined which factors contributed to a Thai fast food restaurant's brand loyalty (BL). From June 2017 to October 2017, the researchers surveyed 20 fast food service restaurants during three service periods. Every fifth customer was randomly selected and asked to fill out the questionnaire, from which the survey achieved a 79.66% response rate (478 questionnaires). The structural equation model (SEM) analysis between variables influencing BL was conducted employing a latent variable LISREL 9.10path analysis. Accuracy interpretation of the SEM on BL made use of a goodness-of-fit (GOF) assessment. Results revealed that all causal variables in the model had a positive influence on Thai fast food restaurant BL, which can be combined to explain the variance of the factors affecting BL (R 2 ) by 78%. Also, BL was shown to be influenced by four variables, and when ranked in importance weremarketing communications (MC), customer satisfaction (ST), brand quality (BQ), and brand value (BV),with TE values equal to 0.88, 0.51, 0.49 and 0.30 respectively.